Thoracolumbar And Lumbopelvic Spinal Alignment During The Deadlift Exercise: A Comparison Between Men And Women - Victor Bengtsson; Ulrika Aasa; Fredrik Öhberg; Lars Berglund (International Journal of Sports Physical Therapy, 2022)
# Background